2019
DOI: 10.1051/0004-6361/201834766
|View full text |Cite
|
Sign up to set email alerts
|

Flattened loose particles from numerical simulations compared to particles collected by Rosetta

Abstract: Context. Cometary dust particles are remnants of the primordial accretion of refractory material that occurred during the initial stages of the Solar System formation. Understanding their physical structure can help constrain their accretion process.Aims. The in situ study of dust particles collected at slow speeds by instruments on-board the Rosetta space mission, including GIADA, MIDAS and COSIMA, can be used to infer the physical properties, size distribution, and typologies of the dust. Methods. We have de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…This finding is in agreement with the observation of the COSIMA instrument, detecting a lack of tens of micrometersized or smaller dust particles in the coma of comet 67P (Merouane et al 2017). Thus, it seems probable that the size of the particles observed by MIDAS is mainly created by fragmentation, which should depend on the initial size before impact, impact speed (Ellerbroek et al 2017), and the interconnected properties such as density and porosity, as well as cohesion (Lasue et al 2019). Thus, it should be noted that all size distributions discussed in Sect.…”
Section: Basic Statistics Of Midas Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in agreement with the observation of the COSIMA instrument, detecting a lack of tens of micrometersized or smaller dust particles in the coma of comet 67P (Merouane et al 2017). Thus, it seems probable that the size of the particles observed by MIDAS is mainly created by fragmentation, which should depend on the initial size before impact, impact speed (Ellerbroek et al 2017), and the interconnected properties such as density and porosity, as well as cohesion (Lasue et al 2019). Thus, it should be noted that all size distributions discussed in Sect.…”
Section: Basic Statistics Of Midas Particlesmentioning
confidence: 99%
“…As the choice of h is crucial, but since the expected MIDAS cluster size is unknown, we orientate on the results of other Rosetta dust instruments and laboratory experiments to set a reasonable value. The bandwidth should be a strong function of the impact velocities as well as initial particle sizes and material strengths (Ellerbroek et al 2017;Lasue et al 2019). However, Ellerbroek et al (2017) found that a large mass loss of the parent particle on impact can be expected in certain cases.…”
Section: Dust Collection Processmentioning
confidence: 99%
“…To study the physical properties of the dust particles coming from different regions, we analysed the dust shape distribution on the four targets. The parameter used as shape descriptor is the flatness (or aspect ratio), defined as = h / √ A , where h and A are the particle height and area, respectively (Lasue et al 2019 ;Kim et al, in preparation). A small F (i.e.…”
Section: Midasmentioning
confidence: 99%
“…They likely resulted from submicron-sized grains accreted at low collision velocities, with further addition of minerals processed near the proto-Sun [e.g. [15][16]. At the Late Heavy Bombardment epoch, enormous influxes of interplanetary dust might then have provided a massive delivery of cometary carbonaceous compounds on telluric planets [1; 17].…”
Section: Significance Of the Results Back In Time And Beyond In Spacementioning
confidence: 99%